Andrew Paxman, En busca del señor Jenkins. Dinero, poder y gringofobia en México, México, Penguin Random House/CIDE, 2016, 604 pp. - Martínez Delgado, Gerardo (América Latina en la Historia Económica, 2017)
No contiene Resumen